Literature Study: Building Adolescent Mental Health by Tackling Toxic Culture Among Teens on Social Media - Ulfah, Ulfah; Surawan, Surawan (Universitas Muhammadiyah Yogyakarta, 2024)
Today's teenagers are active social media users. However, in interacting on social media, people often engage in negative behaviour on social media or toxic culture, which can interfere with adolescent mental health. If allowed to continue, it will be dangerous for the next generation. A toxic culture will cause moral decline in a nation, which will have an impact on the mental health of the community itself. Therefore, this study aims to provide a deeper understanding of how toxic culture on social media impacts the mental health of adolescents. This research uses a qualitative approach with a literature research method. Data analysis in this research uses the content analysis method of the literature that has been collected. The results showed that toxic culture on social media has a significant impact on adolescents' mental health. Forms of toxic culture that are often found on social media are body shaming, cyberbullying, addiction, and the spread of misinformation. It can have an impact on mental health, interpersonal relationships, and academic achievement and encourage risky behavior among adolescents. Therefore, efforts have been made to educate and improve digital literacy, parental guidance and supervision, content moderation, mental support, and community collaboration. These efforts have shown some degree of success. Factors influencing success include commitment and consistency from those involved, active involvement of parents, effective digital content moderation, adequate mental support, and strong community collaboration. However, there are failure factors such as lack of resources and funding, stigma and discrimination towards mental health issues, lack of coordination between stakeholders, resistance to change, and socio-cultural and economic factors.